2021
DOI: 10.1039/d0cp04067c
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the bacterial cell wall in uranium(vi) biosorption

Abstract: The bacterial cell envelope, in particular the cell wall, is considered the main controlling factor in the biosorption of aqueous uranium(vi) by microorganisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Membranes play a major role in sorption of metals where electrostatic interactions between positively charged metal species and negatively charged functional groups (e.g., phosphates and carboxyles) occur. Gram-positive bacteria (such as the Be9 strain) exhibit greater biosorption capacity than Gram-negative bacteria due to their cell envelope components ( Hufton et al, 2021 ). Liu et al (2015) demonstrated the role of carboxyl, phosphoryl, and amino functional groups of Synechococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Membranes play a major role in sorption of metals where electrostatic interactions between positively charged metal species and negatively charged functional groups (e.g., phosphates and carboxyles) occur. Gram-positive bacteria (such as the Be9 strain) exhibit greater biosorption capacity than Gram-negative bacteria due to their cell envelope components ( Hufton et al, 2021 ). Liu et al (2015) demonstrated the role of carboxyl, phosphoryl, and amino functional groups of Synechococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The harvested cells from one suspension were subjected to vacuum drying overnight and the dry weight was measured. The other suspension was subjected to sonication to break cells (complete cell disruption was confirmed by microscopy), and the insoluble fraction containing cell wall and wall-associated proteins ( 55 ) was washed by Milli-Q water. We confirmed that protein mass in the insoluble fraction per total cell mass was about 0.2% based on the Bradford Assay (Bio-Rad Laboratories, Inc.), and, thus the insoluble fraction predominantly consists of cell wall.…”
Section: Methodsmentioning
confidence: 99%
“…Rhizobium immobilizes metal ions on the cell surface through mechanisms such as complexation, coordination, and ion exchange, thereby preventing plant root cells from absorbing excess metals from the soil and causing toxicity [ 120 , 121 ]. For example, phosphate and carboxyl groups associated with Rhizobium cell envelope proteins and phosphorylated biopolymers (such as teichoic acid, surface proteins, and peptidoglycan) mediate uranium (Ur) biosorption, leading to greater accumulation of Ur in the cell envelope [ 122 ]. The mycelium on the surface of the AMF structure adsorbs metal ions and deposits them on the cell wall, and then reduces TMs from one form to another by positively charged particles, including amino acids, thiol groups, and glutathione, etc., to reduce toxicity to plants [ 123 , 124 ].…”
Section: Detoxification Regulation Strategies Of Rhizobium Symbiosis ...mentioning
confidence: 99%